2022
DOI: 10.3390/f13081209
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Tree Growth and Intrinsic Water Use Efficiency to Environmental Factors in Central and Northern China in the Context of Global Warming

Abstract: The Loess Plateau is a fragile ecological zone that is sensitive to climate change. The response, adaptation, and feedback of tree growth in forest ecosystems to global warming and CO2 enrichment are urgent scientific issues. Intrinsic water use efficiency (iWUE) is an important indicator for understanding forest ecosystem adaptability to climate change and CO2 enrichment. In this study, tree-ring width, tree-ring stable carbon isotope ratio (δ13C), and iWUE of P. tabulaeformis Carr. were established. Climate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…In the study area, the intrinsic WUE was significantly negatively correlated with RH (R 2 = 0.02, p < 0.01, Figure 3 h), which was also been found in some previous studies [ 22 , 50 ]. The increase in RH relieves the water stress in plants, which promotes an increase in stomatal conductance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the study area, the intrinsic WUE was significantly negatively correlated with RH (R 2 = 0.02, p < 0.01, Figure 3 h), which was also been found in some previous studies [ 22 , 50 ]. The increase in RH relieves the water stress in plants, which promotes an increase in stomatal conductance.…”
Section: Discussionsupporting
confidence: 88%
“…The range of intrinsic WUE was from 8.61 to 123.39 μmol mol −1 with an average value of 60.66 μmol mol −1 ( Figure 1 b), which was lower than the result from global, arid and semiarid climate regions [ 49 , 50 ]. A previous study showed that the amount of water loss by plants often exceeds the amount of carbon accumulation by three orders of magnitude for terrestrial plants [ 14 ].…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, the increased water use efficiency could indirectly lead to increases in ecosystem leaf index (Y. Zhang et al, 2022). Based on Ren et al's (2022) study of CO 2 and intrinsic water use efficiency (iWUE) within a forest ecosystem on the LP, there is a significant and continuous upward trend in water use efficiency spanning the past three centuries. The primary driver of this long‐term change in water use efficiency is the increasing concentration of atmospheric CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that plants can improve their tolerance by increasing the iWUE values to help them grow under drought stress as water stress increases ( Churakova et al., 2020 ; Yang et al., 2021 ). At the same time, high temperature may reduce stomatal conductivity and the transpiration rate of trees in leaves and increase iWUE ( Granda et al., 2014 ; Hararuk et al., 2019 ), but the increase in iWUE did not offset the negative impact of warming on tree growth ( Ren et al., 2022 ), which drove growth declines of about 50% ( Heilman et al., 2021 ). In the course of plant life, water and carbon are so closely connected that it is difficult to separate them.…”
Section: Introductionmentioning
confidence: 99%